Damage-free light-induced assembly of intestinal bacteria with a bubble-mimetic substrate - Kota Hayashi; Yasuyuki Yamamoto; Mamoru Tamura; Shiho Tokonami; Takuya Iida (Communications Biology, 2021)
Hayashi et al. propose a method to realise rapid, damage-free, remote light-induced assembly of microbes over a submillimeter area with the “bubble-mimetic substrate”. They assemble 104–105 cells of lactic acid bacteria with a survival rate higher than 95% around a laser spot. This technique is promising in developing methods for rapid and high-efficiency functional analysis of microbes.